Proxy measures of premortem cognitive aptitude in postmortem subjects with schizophrenia. Issue 3 (14th February 2020) - Glausier, Jill R.; Kelly, Mary Ann; Salem, Samantha; Chen, Kehui; Lewis, David A.
Abstract: Background: Postmortem human brain studies provide the molecular, cellular, and circuitry levels of resolution essential for the development of mechanistically-novel interventions for cognitive deficits in schizophrenia. However, the absence of measures of premortem cognitive aptitude in postmortem subjects has presented a major challenge to interpreting the relationship between the severity of neural alterations and cognitive deficits within the same subjects. Methods: To begin addressing this challenge, proxy measures of cognitive aptitude were evaluated in postmortem subjects ( N = 507) meeting criteria for schizophrenia, major depressive or bipolar disorder, and unaffected comparison subjects. Specifically, highest levels of educational and occupational attainment of the decedent and their parents were obtained during postmortem psychological autopsies. Results: Consistent with prior findings in living subjects, subjects with schizophrenia had the lowest educational and occupational attainment relative to all other subject groups, and they also failed to show the generational improvement in attainment observed in all other subject groups. Conclusions: Educational and occupational attainment data obtained during postmortem psychological autopsies can be used as proxy measures of premortem cognitive function to interrogate the neural substrate of cognitive dysfunction in schizophrenia.